Effect of calcium hydroxide (Ca(OH)2) and magnesium sulfate (MgSO4) on vaname shrimp (Litopenaeus vannamei) cultivation in freshwater media - Scabra, Andre Rachmat; Marzuki, Muhammad; Rizaldi, Alwan (Acta Aquatica: Aquatic Sciences Journal, 2023)
The purpose of this study was to determine the effect of giving the ratio of Calcium Hydroxide (Ca(OH)2) and Magnesium Sulfate (MgSO4) with different doses on the growth of white shrimp (Litopenaeus vannamei) production in freshwater media. This research was conducted by experimental method using Completely Randomized Design (CRD). The parameter studied was how the effect of the addition of Ca(OH)2 and Magnesium Sulfat (MgSO4) lime with different doses in the maintenance container with 5 treatments and 3 replications, so that 15 experiments were obtained. The treatments applied were: Treatment 1 (P1) Seawater without the addition of calcium and magnesium, P2 Freshwater + 80 ppm Ca(OH)2, P3 Freshwater + 80 ppm Ca(OH)2 and 40 ppm MgSO4, P4 Freshwater + 80 ppm Ca(OH)2 and 80 ppm MgSO4, and P5 Freshwater + 80 ppm Ca(OH)2 and 120 ppm MgSO4. The results showed that the highest survival rate using fresh water was at P4 which was 82%, the specific weight growth rate was 3.9%, and the specific length growth rate was 2.6%. the value of the feed conversion ratio is 0.8. For water quality parameters, the temperature ranges from 30.4-30.60C, water pH 7.2-8.2, DO 6.4-6.6 mg/L, Alkalinity 68-72 ppm, and Ammonia 0.1 mg /L.Keywords: Ca(OH)2; Freshwater; MgSO4; Vannamei Shrimp